First-order hyperpolarizabilities of chiral, polymer-wrapped single-walled carbon nanotubes. Issue 82 (23rd September 2016) - Depotter, Griet; Olivier, Jean-Hubert; Glesner, Mary G.; Deria, Pravas; Bai, Yusong; Bullard, George; Kumbhar, Amar S.; Therien, Michael J.; Clays, Koen
Abstract : Manipulation of polymer electronic structure provides a new means to modulate the first-order hyperpolarizabilities ( β HRS values) of chiral, individualized polymer-wrapped single-walled carbon nanotube superstructures at a telecommunication-relevant wavelength (1280 nm). Abstract : We report the first-order hyperpolarizabilities ( β HRS values) of individualized, length-sorted (700 ± 50 nm long) (6, 5) SWNTs and corresponding polymer-wrapped (6, 5) SWNT superstructures. These SWNT-based nanohybrids feature semiconducting polymers that wrap the SWNT surface in an exclusive left-handed helical fashion. Manipulation of the polymer electronic structures in these well-defined nanoscale objects provides a new avenue to modulate the magnitude of β HRS at long wavelength (1280 nm).